(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
Water contamination management is currently one of main focus areas of the scientific study. While colored organic molecules typically contribute just a small percentage of the influent to municipal wastewater, their hue makes them visually unattractive. Stringent regulatory procedures are pushing businesses to clean their wastes effluents to progressively high standards. For example, as indicated by the quantity of relevant research publications, pigment removal has recently been a subject of major scientific interest. Several decolorization technologies have been published during the previous two decades, but only a handful have been embraced by specific industries. Alternative treatments, like biological and system performed, that are efficient in reducing dyes or colorants from large volumes of effluents and therefore are cost effective are needed. This article discusses among the most widely used, and also most potential, decolorization processes for industrial effluents. The decolorizing effectiveness of different causal agents is studied using a variety of physical, chemical, but also biological approaches. Furthermore, a critical assessment of various treatment procedures and emerging technology is presented, together with comments on their advantages and disadvantages.